Power Spectral Analysis of Heart Rate Variability in Adolescent Male Athletes - Alom, Md Mashudul; Begum, Noorzahan; Ferdousi, Sultana; Begum, Shelina; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2010)
Background: Cardiac autonomic nervous activities (CANA) deteriorate with age, obesity, sedentary life style and in various cardiac and noncardiac disease conditions. Regular physical exercise may improve CANA in health and diseases. Power spectral analysis (PSA) of Heart rate variability (HRV) is one of the most promising newer techniques to quantify CANA. Objective: To analyze HRV by Power Spectral method in order to find out the influence of regular physical exercise on CANA in male adolescent athletes. Method: This cross sectional study was carried out on 62 adolescent male athletes aged 12-18 years (group B), in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University from 1st July 2007 to 30th June 2008. For comparison, 30 age, sex, BMI and socioeconomic condition matched apparently healthy sedentary subjects (group A) were also studied. The study subjects were selected from the BKSP (Bangladesh Krira Shikka Prothistan, Savar, Dhaka) and the control from a residential school of Dhaka city.Power spectral measures of HRV including Total Power (TP), Very Low Frequency Power (VLF) Low Frequency (LF), High Frequency (HF) LF/HF were measured by a Polygraph. For statistical analysis, Independent-Sample t-test was used. Results: Total power, HFnu power and the VLF, LF, HF were significantly (P<0.001) higher and LFnu power and the LF/HF ratio were significantly (P<0.001) lower in athletes than those of nonathletes which indicate higher cardiac parasympathetic and lower sympathetic activity in athletes. Conclusion: Cardiac Autonomic regulation with increased parasympathetic and decreased sympathetic modulation may occur with in athletes engaged with regular physical exercise. Key words: Power Spectral Analysis (PSA), CANA, Athlete, Adolescent DOI: 10.3329/jbsp.v4i2.4169 J Bangladesh Soc Physiol. 2009 Dec;4(2): 26-33